Blindness And Sight In Ralph Ellison's Invisible Man - زينة كمال ابراهيم (College of Education for Women, 2019)
The Civil Rights era has been an era of struggle for the African American in the Unites states. Thus, many writers devoted their writing to reflect the racism and discrimination that many have suffered from, among them is Ralph Ellison. Ralph Ellison is a 20th century African-American writer and scholar best known for his renowned, award-winning novel Invisible Man. He illustrates the powerful social and political forces that conspire to keep black Americans in their place, denying them the right to life, liberty, and the pursuit of happiness guaranteed to all Americans. Invisible Man is a 1952 novel that addresses many of the social and intellectual issues facing African-Americans in the twentieth century. It examines two key-concepts of the 40-50's black literature: blindness and sight in racism. Presenting the concepts of blindness and sight, Ellison introduces the reader to the complex nature of this problem and its subjacent factors. It is told in the form of a first-person narrative, Invisible Man traces the nameless narrator's physical and psychological journey from blind ignorance to enlightened awareness. It is the story of a young , college educated black man struggling to survive and succeed in a racially divided society that refuses to see him as a human being. Thus, this research paper begins with an introduction which gives an account of the novel and highlights in the writer's life, Ralph Ellison. The body analyzes the novel of Invisible man, through the blindness and sight of the characters. The conclusion sums up the findings of the research paper.